2015
DOI: 10.1111/jeb.12634
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evolutionary analysis of tributyltin‐binding protein and pufferfish saxitoxin and tetrodotoxin‐binding protein genes in toxic and nontoxic pufferfishes

Abstract: Understanding the evolutionary mechanisms of toxin accumulation in pufferfishes has been long-standing problem in toxicology and evolutionary biology. Pufferfish saxitoxin and tetrodotoxin-binding protein (PSTBP) is involved in the transport and accumulation of tetrodotoxin and is one of the most intriguing proteins related to the toxicity of pufferfishes. PSTBPs are fusion proteins consisting of two tandem repeated tributyltin-binding protein type 2 (TBT-bp2) domains. In this study, we examined the evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Nevertheless, Tetraodontidae was not recommended for human consumption. Hashiguchi et al (2015) reported that family Tetraodontidae or pufferfish contained tetrodotoxin and saxitoxin in their organs and the degree of toxicity was highly variable even within each toxic species. Tetrodotoxin in the pufferfish localized in the ovary of its larvae as protection against predators (Itoi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Tetraodontidae was not recommended for human consumption. Hashiguchi et al (2015) reported that family Tetraodontidae or pufferfish contained tetrodotoxin and saxitoxin in their organs and the degree of toxicity was highly variable even within each toxic species. Tetrodotoxin in the pufferfish localized in the ovary of its larvae as protection against predators (Itoi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PSTBP is assumed to be a carrier protein that transfers TTX among tissues in toxic species of pufferfish in the genus Takifugu . Hashiguchi et al [ 41 ] examined PSTBP genes in five toxic species of pufferfish in the genus Takifugu and three non-toxic species of pufferfish ( L. wheeleri (at present L. spadiceus ), L. gloveri (at present L. cheesemanii ) and S. pachygaster ). PSTBP genes were cloned in the genus Takifugu , while they were not obtained in the three non-toxic pufferfish.…”
Section: Discussionmentioning
confidence: 99%
“…The difference of toxin distribution pattern between Takifugu and Arothron is probably caused by the difference of some proteins which are implicated in TTX accumulation system. We previously found a glycoprotein, named as PSTBP (puffer fish saxitoxin and tetrodotoxin binding protein), that binds to TTX and STX in the blood plasma of Takifugu pardalis [ 51 ], and also, it was reported that PSTBP was commonly detected in several Takifugu species [ 52 , 53 ]. We are planning to examine the presence of PSTBP-like protein in Arothron species to get a hint that will help explain the difference of TTX-accumulation tissues between Takifugu and Arothron genus.…”
Section: Discussionmentioning
confidence: 99%